226k views
3 votes
Short Response #3: Justify each step of the equation solved below using mathematical properties.(4 points)1.-3(x + 2) + 4 = 94Given132.-3x - 6 + 4 = 9413.3. -3x - 2 = 941414.4.-3x = 9615 15.5. X = -3216 16.

User Jerri
by
5.0k points

1 Answer

4 votes

We are given the equation

-3(x + 2) + 4 = 94

Firstly, open the parenthesis by multiplying through by -3

-3 * x + -3(2) + 4 = 94

-3x - 6 + 4 = 94

-6 + 4 = -2

-3x - 2 = 94

Collect the like terms

-3x = 94 + 2

-3x = 96

Divide both sides by -3

-3x /-3 = 96/-3

x = -96/3

x = -32

User Badgley
by
5.4k points